Complementary and alternative medicines in oral health care: An integrative review - Basem Mohammed Abuzenada; Fawaz Pullishery; Mohamed Samir Abdelmagid Elnawawy; Samaher Abdullah Alshehri; Rowayda Mohammed Basheer Alostath; Batool Mabrook Bakhubira; Walaa Farhan Amerdash (Wolters Kluwer Medknow Publications, 2021)
Complementary and alternative medicine (CAM) uses a holistic approach that finds natural solutions that help the immune system to fight off infection and diseases. In conventional medicine, the diseases are treated as a series of symptoms developed and not its actual cause or etiology, but CAM commonly targets the exact cause of the disorder thereby stimulating the body's healing process. This is based on an integrative literature review of methods and techniques used as complementary and alternative approaches for oral health care. A comprehensive electronic database search was conducted in PubMed, CINAHL, MEDLINE, EMBASE, Google, Google Scholar, and SCOPUS. Medicinal plants such as Medicago Sativa, Aloe Barbadensis Miller (Aloe Vera), and Trifolium Pratense (Red Clover) have excellent applications in treating gum disorders, prevent tooth decay, and have demonstrated good antifungal activity in the oral cavity. Homeopathic medicines such as Belladonna, Antimonium crudum, and Chamomilla have useful applications in relieving toothache. In Chinese medicine, various acupressure points (Acupuncture) have been used to relieve pain related to tooth, head-and-neck region, sinusitis, etc. Dental professionals can utilize these treatment modalities in their practice along with other conventional procedures as an integrative treatment approach to achieve better outcomes.